Ozonate Your Implants - Shah, Rohit; Talati, Meenakshi; Mitra, Dipika; Rodrigues, Silvia; Shetty, Gaurav; Prithyani, Saurabh; Vijayakar, Harshad (International Journal For Research In Health Sciences And Nursing, 2018)
The oral cavity appears as an open ecosystem, and with oral biofilm formation and development,the inside selection of specific microorganisms have been correlated with the most common oral pathologies including peri-implantitis. The mechanical removal of the biofilm and adjunctive use of antibiotic disinfectants or various antibiotics have been the conventional methods for periodontal therapy. Ozone (O3) is a triatomic molecule, consisting of three oxygen atoms, and its application in medicine and dentistry has been successfully indicated for the treatment of 260 different pathologies. The ozone therapy has been more beneficial than present conventional therapeutic modalities that follow a minimally invasive and conservative application to dental treatment. Hence this short communication attempts to review the use of ozone in implant dentistry.